ANALYZING MEDIATION EFFECT OF COMPETITIVE ADVANTAGE ON FIRM PERFORMANCE AS MEASURED BY TOTAL QUALITY MANAGEMENT AND SUPPLY CHAIN MANAGEMENT - Ramlawati, Ramlawati; Murniati, Sitti; Haditomo, Alfabetian Harjuno Condro; Mambuhu, Nurmawati; Indriakati, Andi Jenni; Fitriana, Fitriana (Universitas Brawijaya, Indonesia, 2022)
The objective of this research is to examine 4 (four) variables, respectively total quality management, supply chain management, competitive advantage, and firm performance. The research type is quantitative. Statistic data were analyzed using SmartPLS version 3.0. The subject of research was book writers at Optima Publikasi Literasi Makassar. The research was done in Optima Publikasi Literasi Makassar, which published and printed books. The research population comprised of book writers at Optima Publikasi Literasi Makassar, which as of November 2020 was counted for 334. Slovin Equation was used on the population, which produced 77 respondents as a research sample. Primary data were collected through a questionnaire. The results showed that better total quality management has an optimization effect on competitive advantage. Better supply chain management delivers a high competitive advantage. Better total quality management has an optimization effect on firm performance. Better supply chain management optimizes firm performance. High competitive advantage has optimization effect on firm performance by improving innovative capacity and increasing competitiveness. Better total quality management optimizes firm performance through competitive advantage by improving firm aspects relating to quality control and competitiveness. Better supply chain management optimizes firm performance through high competitive advantage. Better total quality management has implications for increasing the competitiveness and performance of the company.